Determinants of corruption and its impact on firm performance: Global evidence - Syed Muhammad Imran; Hafeez Ur Rehman; Rana Ejaz Ali Khan (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2019)
This paper examines two important aspects of the firms, firstly, it identifies the factors responsible for firm-level corruption, and secondly it investigates the impact of corruption on firm performance in 147 economies using the data set of World Bank's Enterprise Survey. Two indicators, that is, firm's annual real sale growth and export performance are used to gauge the firm performance. Logistic regression is employed to estimate the determinants of corruption and Ordinary Least Square is employed to estimatethe impact of firm's corruption on its performance. It is found that corruption augments firm'ssale and export performances in the aggregate analysis of 147 economies. In the disaggregated analysis, it is found that corruption increases the firm's sale and exports in low income economies while it reduces the firm's performance in high and middle income nations.
Keywords: 330; corruption; product innovation; firm performance; bureaucratic hurdles; export performance